PENGARUH KONVERGENSI IFRS TERHADAP KUALITAS LAPORAN KEUANGAN PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Raden Rosiyana Dewi; Noviola Kaseh (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2011)
This study was conducted to examine the effect of the third application of IAadoption of IFRS (namely PSAK 13 on Investment Property, PSAK 16 on Fixed Assets and PSAK 30 on Rent) particularly on the financial statements of the company. Test conducted on the influence of the application of the convergence of financial performanc as seen from the level of company size, activity, Solvency, Growth, Profitability, an Investment company performance and Testing the effect of convergence on the valu relevance of financial information from the company viewed the relevance value ne income and equity book value to price company stock. The study uses secondary data from the Indonesia Stock Exchange and th Indonesian Capital Market Directory (ICMD) in 2008 and 2009. From 149 non-financia companies (outside the Bank, not Banks Financial Institutions, Securities, an Insurance) with certain criteria, the authors obtained 100 companies are selected a testing samples of a Hypothesis one (H1), whereas samples testing hypothesis two (H2 using the 80 companies. Testing the hypothesis using two models of regression, testin hypothesis one (H1) using the Logistic Regression model (logit) and testing th hypothesis two (H2) using OLS linear regression model. Based on the results of dat analysis, the conclusion that the application of PSAK to IFRS convergence significan effect on financial performance and increased relevance value.Keywords: Convergence GAAP to IFRS, Financial Performance, Value Relevance o Earnings and Book Value Equity.